Factors that Influence to Costumers Sharia Bank Loyalty: An Empirical Study of Students at Universitas Darussalam Gontor Ponorogo - Rofiqo, Azidni; Wicaksana, Febrian Arif; Abd Razak, Abdurrizqi Bin (Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: The purpose of this research is to predict customer satisfaction, customer perceived value, and customer Islamic religiosity on Sharia bank customer loyalty. Research Methods: The research used a quantitative approach with 140 respondents who were Sharia bank customers, specifically students at Universitas Darussalam Gontor, Ponorogo. A Likert scale of 1-5 was employed for measurement, and partial least squares–structural equation modeling was used to analyze the data. Results: The results of this research demonstrate that customer satisfaction, perceived value, and Islamic religiosity have a significantly positive impact on Sharia bank customer loyalty. Conclusion: To build and maintain customer loyalty, Islamic banks must leverage customer satisfaction, value, and religiosity by offering a variety of Sharia-based products and services that truly differentiate them from conventional banks.